Hepatitis B among young people in Lere health department (Chad) - Djongali Tchonchimbo; Ali Mahamat Moussa; Gabkika Bray Madoue; Djongali Berniba; Julian Süsstrunk (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Background: Hepatitis B is an infectious disease that affects many people worldwide. It may be acute or chronic. Age-specific prevalence varies by geographical region with highest endemicity levels in sub-Saharan Africa and prevalence below 2% in regions such as tropical and central Latin America, North America and Western Europe. Objective: To determine the frequency and characteristics of infected persons with hepatitis B among people from the Lere health department. Participants and method: A 2-month cross-sectional survey was performed in eleven villages in the Lere health department, Chad. At least 100 young people were screened in each village giving a total study population of 1,150 (607 males and 543 females aged ≤ 25 years). Those immunized against hepatitis B were excluded. Studied variables were: age, sex, ethnic group and the results of testing. Results: Hepatitis B tests were positive in 268 cases (23.3%) - 95% of these were from the Moundang ethnic group. Thirty two per cent of boys and 19% of girls aged ≤15 years were infected; 25% of boys and 13% of girls aged over 15 years were infected. Conclusion: This study shows a high prevalence of hepatitis B in a rural area in Chad. The high proportion among youths aged ≤15 years indicates that the main way of infection is likely to be the fetal- maternal transmission.